2012
DOI: 10.3892/or.2012.1864
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinase-2 and -9 in the sera and in the urine of human oncocytoma and renal cell carcinoma

Abstract: Abstract. Matrix metalloproteinases (MMPs) are a family of zinc-dependent endopeptidases, capable of degrading all the molecular components of extracellular matrix. MMPs have been shown to play critical roles in tumor cell invasion and metastasis. We verified the activity of MMPs in the sera and in the urine of patients with kidney carcinoma by gelatin zymography. Of these patients, 16 had clear cell renal carcinoma (ccRCC) and 4 patients had oncocytoma. The sera and the urine of 16 healthy subjects were used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 21 publications
(16 reference statements)
1
19
1
1
Order By: Relevance
“…In renal cell carcinoma using a zymography technique, it has been shown that MMP-9 levels were higher in the serums from clear cell carcinoma in comparison to levels from oncocytoma patients. The prevailing enhanced MMP-9 lytic activity was abundantly present in clear cell carcinoma, whereas MMP-2 activity values were detected in far lesser concentrations [190]. These results were further confirmed by the same author in a study where MMP-9 levels were increased in the clear cell carcinoma patients versus the oncocytoma patients.…”
Section: Gelatinases (Mmp-2 Mmp-9)supporting
confidence: 77%
“…In renal cell carcinoma using a zymography technique, it has been shown that MMP-9 levels were higher in the serums from clear cell carcinoma in comparison to levels from oncocytoma patients. The prevailing enhanced MMP-9 lytic activity was abundantly present in clear cell carcinoma, whereas MMP-2 activity values were detected in far lesser concentrations [190]. These results were further confirmed by the same author in a study where MMP-9 levels were increased in the clear cell carcinoma patients versus the oncocytoma patients.…”
Section: Gelatinases (Mmp-2 Mmp-9)supporting
confidence: 77%
“…As a family of zinc-containing endopeptidases, matrix metalloproteinases (MMPs) are the major enzymes involved in ECM degradation [30,31]. Two representative members, MMP-2 and MMP-9, were reported highly expressed in invasive tumours [32,33]. The expression of MMP-2 and MMP-9 was reduced after re-expression of DACH1 in GC cells, and this relationship was confirmed by knocking down DACH1 in GES-1 cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Particularly, the high expression of MMP-9 is considered as a crucial factor for cell migration/invasion of endothelial cells into the adjacent stroma (30). It is essential to elucidate the molecular mechanisms underlying the N-glycan regulation of the invasive function of MMP-9 in gastric cancer biology.…”
Section: Expression Of Invasion-related Factors In the Bgc823/gnt-v Cmentioning
confidence: 99%
“…Furthermore, EGFR expression has also been shown to correlate with MMP expression in breast cancer cell lines and non-small cell lung cancer (15,26). MMPs are a family of zinc-containing endopeptidases, among which, MMP-2 and MMP-9 are highly expressed in aggressive tumors (27)(28)(29)(30). However, the precise mechanism of GnT-V regarding the association of EGFR signaling, EMT and MMPs in gastric cancer still remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%